The contributions of the military nurse and the factors that affect these contributions - Bontigao, Erlinda B. (1980)
The role of the military nurse in the Armed Forces of the Philippines seems to be understated when compared to that of her more militarily active brothers-in-arms. Nevertheless, the part she plays in the military organization is a vital and critical 1 because, like her male counterparts, she also makes significant contributions to nation-building and national defense. This becomes more apparent when 1 considers the archipelagic nature of our country and the wide dispersal of component units of the armed forces over far-flung areas. Under these circumstances could ill-afford to sustain heavy casualties, either through military action or illness. This is where the military nurse enters the picture for it is her principal mission to help restore the health of sick or wounded personnel so that they could be returned to active duty within the shortest possible time. In this way, the military nurse helps maintain the numerical strength and combat readiness of the armed forces. Despite the key role that the military nurse performs in the military organization, so little has been written about her duties, activities, responsibilities, and other aspects of her job in the armed forces of our country. Empirical work on the subject is even more scanty. This masteral thesis therefore seeks to augment the limited literature on military nursing although it cannot claim to completely remedy-this paucity of material. This study focuses on the contributions of the military nurse to the hospital and military organization. 3 kinds of contributions are covered-professional, administrative and national security. In this study, the linkages of these contributions to individual attributes, family-related characteristics, and work-related factors are to be established. On the basis of the above findings, the investigator recommends that further training of military nurses should be emphasized; that individual and group research on military nursing be encouraged; that recruitment priorities should be given to nurses with at least a BSN degree; and that, in the selection of applicants, the variables of age, education and civil status be seriously considered.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Military nursing; Nursing